(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The study was carried out to develop a wet litter model with magnesium chloride to assess the effectiveness of a polyherbal formulation (PHF) on growth performance, litter and cecal moisture (LCM) level, cecal consistency (CC) score, and footpad lesions (FPLs) score in Ross 308 broiler chickens. Materials and Methods: 1,200 one-day-old chicks were assigned into five groups: normal control, negative control [NTC; treated with 1.7% magnesium chloride hexahydrate (MgCl2.6H2O)], and three treatment groups, T1, T2, and T3, where 750, 1,000, and 2,000 gm/ton of PHF, respectively, were supplemented. All the groups were fed a basal diet until day 7. However, the NTC and treatment groups were fed a diet with MgCl2 from days 8 to 42. Results: The addition of MgCl2 for 35 days worsened the growth performance traits in broilers and induced wet litter problems (FPL, high LCM, and poor CC) in the NTC group. However, PHF (750, 1,000, and 2,000 gm/ton) ameliorated the negative effect of a diet with MgCl2 on growth performance and wet litter problems, but a better response with respect to LCM and CC was observed in 2,000 gm/ton of PHF group, followed by that in 1,000 gm/ton of PHF group and 750 gm/ton of PHF group on day 42. Conclusion: The wet litter broiler model was developed through excessive feeding of MgCl2, which caused the performance parameters to worsen and the emergence of problems associated with the wet litter. Supplementation with PHF ameliorated these problems and, therefore, it can be used for the management of wet litter in poultry. J. Adv. Vet. Anim. Res., 6(4): 536-543, December 2019